2013 35th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2013
DOI: 10.1109/embc.2013.6610793
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a wrist monitor for accurate estimation of RR intervals during sleep

Abstract: While the incidence of sleep disorders is continuously increasing in western societies, there is a clear demand for technologies to asses sleep-related parameters in ambulatory scenarios. The present study introduces a novel concept of accurate sensor to measure RR intervals via the analysis of photo-plethysmographic signals recorded at the wrist. In a cohort of 26 subjects undergoing full night polysomnography, the wrist device provided RR interval estimates in agreement with RR intervals as measured from sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…HR measurement was found to be very accurate, with a high correlation between the devices. This is in line with previous findings suggesting good accuracy [3][4][5]. Indeed, the RMSE for HR measurement was constantly low despite all confounding factors.…”
Section: Heart Ratesupporting
confidence: 93%
See 1 more Smart Citation
“…HR measurement was found to be very accurate, with a high correlation between the devices. This is in line with previous findings suggesting good accuracy [3][4][5]. Indeed, the RMSE for HR measurement was constantly low despite all confounding factors.…”
Section: Heart Ratesupporting
confidence: 93%
“…The clinical signs most commonly associated with patient deterioration are arterial blood oxygen saturation (SpO 2 ), heart rate (HR), respiratory rate (RR), and blood pressure [2]. There is presently no single device capable of wirelessly monitoring all of these parameters, although several reports describe attempts to develop such a device [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have recently assessed the performances of wearable devices, such as smart bands, in monitoring physiological changes while walking, running or sleeping [ 26 ]. However, such devices have strong limitations, such as low perfusion in the wrist area and unstable beat detection due to motion [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…None of the commercially available smartwatches are able to provide such data rate yet. In contrast, Renevey et al [19] have demonstrated a proprietary wrist-worn devices capable of measuring RR intervals in real-time. The future studies aiming to embedded wrist-worn CEDs for physiological tracking in driving context should address this limitation.…”
Section: Discussionmentioning
confidence: 99%